(untitled) (Journal of Economic Research & Business Administration, 2016)
In the transition to an innovation economy, the role of a person with his education, qualifications and experience in ensuring economic growth and improving the competitiveness of the state. The major component of the human capital is labor, its quality and performance. In its turn quality of work is determined by the mentality of the population and quality of life. Unfortunately, the work in Kazakhstan remains a traditionally poor quality, as demonstrated by production of the majority of domestic enterprises, which is uncompetitive on world markets. Low-performance and low-quality labor significantly reduces the accumulation of human capital of Kazakhstan. The idea and practice of reproduction and functioning of the human capital become more complex and filled with new content. This human capital is gaining recognition and development in a rather wide sense – from the individual to the world community. Human capital is becoming a mass phenomenon, it corresponds to the type of innovative reproduction.